Acute jejunal diverticulitis presenting with perforation peritonitis: a rare case managed in a rural setup - Kumbhar, Hiren V.; Prabhu, Namita; Kadam, Shantanu; Deshmukh, Vasant (International Surgery Journal, 2025)
Jejunal diverticulosis is an uncommon and frequently underdiagnosed condition of the small intestine, typically presenting in elderly patients with nonspecific gastrointestinal symptoms. Complications such as hemorrhage, obstruction, and perforation, though rare, can be life-threatening and require prompt diagnosis and surgical management. Here’s a report of rare case of acute jejunal diverticulitis with perforation in a 76-year-old female presenting with generalized abdominal pain, distension, and constipation for four days. The patient, with a history of diabetes mellitus and ischemic heart disease, exhibited febrile tachycardia, tachypnea, hypotension, and generalized abdominal tenderness on examination. Laboratory investigations revealed leucocytosis and borderline renal dysfunction. Abdominal radiography demonstrated pneumoperitoneum, warranting emergency laparotomy. Intraoperatively, multiple jejunal diverticula were identified along the mesenteric border, with a 0.5×0.5 cm perforation located approximately 2 feet distal to the duodenojejunal junction. Segmental resection of the perforated portion with primary end-to-end jejunojejunal anastomosis and thorough peritoneal lavage was performed. The postoperative period was uneventful. Histopathology confirmed true diverticula with perforation. Perforation in jejunal diverticulitis occurs in about 82% of cases due to necrotizing inflammation and may present as generalized peritonitis. Diagnosis relies heavily on computed tomography (CT) imaging, but in resource-limited rural settings, clinical acumen and plain radiographs remain crucial. Prompt surgical intervention remains the mainstay of management to prevent complications such as sepsis and short bowel syndrome. This case highlights the diagnostic challenges and emphasizes the importance of early clinical suspicion and timely surgical management of jejunal diverticular perforation, even in rural healthcare settings with limited resources.